Peran Knowledge Management Dalam Meningkatkan Kinerja Perguruan Tinggi - Jane, Orpha (Jurnal Administrasi Bisnis, 2009)
As the information technology become one of the production factors in human life,knowledge is the important factor for the organization. Toffler, Drucker, Nonaka andsome others say that with the knowledge firm or organization can win the competitionin this post millennium era.Higher Education Institution (HEI) as an organization can also use knowledgeas a management tools. Moreover, it can be one of the engine that can help them toachieve the goals such as improve the performance of HEI to support the studentsand community.In this paper, author argue that the implementation of Knowledge Managementin HEI will be improve the performance of HEI in doing âTridharma PerguruanTinggiâ. However, the implementation is not only refer to the use of some informationtechnology tools, but also with the creation of learning organization.Keywords: Knowledge, performance improvement,learning organization